Animal Models of Tourette Syndrome—From Proliferation to Standardization - Yael, Dorin; Israelashvili, Michal; Bar-Gad, Izhar (Frontiers in Neuroscience, 2016)
Tourette syndrome (TS) is a childhood onset disorder characterized by motor and vocal tics and associated with multiple comorbid symptoms. Over the last decade, the accumulation of findings from TS patients and the emergence of new technologies have led to the development of novel animal models with high construct validity. In addition, animal models which were previously associated with other disorders were recently attributed to TS. The proliferation of TS animal models has accelerated TS research and provided a better understanding of the mechanism underlying the disorder. This newfound success generates novel challenges, since the conclusions that can be drawn from TS animal model studies are constrained by the considerable variation across models. Typically, each animal model examines a specific subset of deficits and centers on one field of research (physiology/genetics/pharmacology/etc.). Moreover, different studies do not use a standard lexicon to characterize different properties of the model. These factors hinder the evaluation of individual model validity as well as the comparison across models, leading to a formation of a fuzzy, segregated landscape of TS pathophysiology. Here, we call for a standardization process in the study of TS animal models as the next logical step. We believe that a generation of standard examination criteria will improve the utility of these models and enable their consolidation into a general framework. This should lead to a better understanding of these models and their relationship to TS, thereby improving the research of the mechanism underlying this disorder and aiding the development of new treatments.